1987
DOI: 10.1177/001440298705400202
|View full text |Cite
|
Sign up to set email alerts
|

Parent Participation by Ethnicity: A Comparison of Hispanic, Black, and Anglo Families

Abstract: This article describes the results of a study of Hispanic parents' satisfaction with and participation in their child's special education program and compares their responses to those of Black and Anglo families from earlier investigations. Sixty-three parents of children receiving special education services were interviewed in Spanish in their homes by trained interviewers who were also parents of handicapped students. Results of the study indicated that Hispanic parents were generally very satisfied with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 7 publications
2
69
0
3
Order By: Relevance
“…Moles (1993) wrote of "disadvantaged parents"-those with low income and minority status-having less involvement in school by teacher report. Lynch and Stein (1987) reported that Hispanic and African American parents offered fewer suggestions at special education meetings and knew significantly less about their children's special services than did Caucasian parents. Although minority status has been identified as a risk factor for PI, little research has examined the different pattern of relations among other family and demographic risk factors and PI within the context of separate minority groups.…”
mentioning
confidence: 99%
“…Moles (1993) wrote of "disadvantaged parents"-those with low income and minority status-having less involvement in school by teacher report. Lynch and Stein (1987) reported that Hispanic and African American parents offered fewer suggestions at special education meetings and knew significantly less about their children's special services than did Caucasian parents. Although minority status has been identified as a risk factor for PI, little research has examined the different pattern of relations among other family and demographic risk factors and PI within the context of separate minority groups.…”
mentioning
confidence: 99%
“…This might be due to the advice of professionals, who advise parents to use the oral method only and discourage the use of sign. Previously cited research showed that Hispanic parents regard educators and medical professionals as absolute authorities (Lynch & Stein, 1987;Salas-Provance et al, 2002) . Thus, when these professionals give such advice, it is unlikely that the Hispanic parents would question them.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Mexican-American mothers believed that educational decisions should be left entirely up to the teacher and the school. Lynch and Stein (1987), in a study that compared parental involvement in school activities, found that Hispanic families participated far less than Black and Anglo families. The authors speculated that the reason for this was that Hispanic parents perceived that the professionals in the education system were more knowledgeable than they were; therefore, they knew better how to handle and meet the needs of their child with a disability.…”
Section: Hispanic Conceptions Of Disabilitymentioning
confidence: 99%
“…Research on barriers has explored a narrowly conceived set of variables and, in doing so, has focused on the participation of special subgroups such as parents from lower socioeconomic and ethnic minority backgrounds and parents of special education students. The result is that a variety of familial, cultural, racial, job, social class, communication, and school personnel attitude factors have been implicated (e.g., Chavkin & Williams, 1989, Comer, 1988Davies, 1988;Epstein, 1986Epstein, , 1987 Klimes-Dougan, Lopez, Adelman, Nelson, 1992;Lopez, 1992;Lynch Stein, 1987;Mannan & Blackwell, 1992;Pennekamp & Freeman, 1988;Stevenson, Chen, & Uttal;Tangri & Leitch, 19821. However, because the studies are correlational, causal relationships have not been established. Furthermore, withingroup variations are rarely explored.…”
Section: Barriers To Involvementmentioning
confidence: 99%